profile
Опубликовано - 2 месяца назад | По предмету Математика | автор Аноним

(х-2)(х+1)-(х-1)(х+2)+0,2=0

  1. Ответ
    Ответ дан Киселёва Саша

    (х - 2)(х + 1) - (х - 1)(х + 2) + 0,2 = 0;

    n

    (х^2 + x - 2x - 2) - (x^2 + 2x - x - 2) + 0,2 = 0;

    n

    x^2 - x - 2 - (x^2 + x - 2) + 0,2 = 0;

    n

    x^2 - x - 2 - x^2 - x + 2 + 0,2 = 0;

    n

    x^2 - x^2 - x - x + 2 - 2 + 0,2 = 0;

    n

    -2x + 0,2 = 0;

    n

    -2x = -0,2;

    n

    x = -0,2 : (-2);

    n

    х = 0,1.

    n

    Проверка:

    n

    (0,1 - 2)(0,1 + 1) - (0,1 - 1)(0,1 + 2) + 0,2 = 0;

    n

    -1,9 * 1,1 - (-0,9 * 2,1) + 0,2 = 0;

    n

    -2,09 - (-1,89) + 0,2 = 0;

    n

    -2,09 + 1,89 + 0,2 = 0;

    n

    -0,2 + 0,2 = 0;

    n

    0 = 0.

    n

    Ответ: х = 0,1.

    0



Топ пользователи